RELATIONSHIP OF SELF-ESTEEM, SELF-EFFICACY WITH SUBJECTIVE WELL-BEING IN LOW-INCOME STUDENTS - Naomi, Deby; Wahyuni, Eka; hidayat, Dede Rahmat (LP2M IAI Al-Khairat Pamekasan, 2026)
Subjective well-being among vocational high school students from low socio-economic backgrounds represents a critical issue in vocational education, as it is closely related to psychological readiness, learning motivation, and academic adjustment. This study aimed to examine the relationship between self-esteem and self-efficacy with subjective well-being among vocational high school students from low socio-economic families. A quantitative approach with a correlational research design was employed. The participants consisted of 250 vocational high school students selected using purposive sampling. Data were collected through subjective well-being, self-esteem, and self-efficacy questionnaires that had been tested for validity and reliability. Data analysis was conducted using parametric statistical techniques, including correlation and multiple regression analyses. The results indicated that self-esteem had a positive and significant relationship with subjective well-being. Similarly, self-efficacy was found to have a positive and significant relationship with subjective well-being. Simultaneously, self-esteem and self-efficacy significantly contributed to students’ subjective well-being. These findings suggest that internal psychological factors play an essential role in shaping students’ subjective well-being, particularly among those facing socio-economic constraints. This study highlights the importance of strengthening self-esteem and self-efficacy through school-based guidance and counseling services as a strategic effort to enhance the subjective well-being of vocational high school students from low socio-economic backgrounds. The findings are expected to provide empirical evidence for the development of more contextual and sustainable psychological intervention programs in vocational education settings.